Karakteristik Sifat Mekanik dan Struktur Mikro Total Knee Joint dari Paduan Co-26Cr-6Mo-0,18N Hasil Pengerjaan Panas [The Characteristics of Mechanical Properties and Microstructures on Hot-treated Co-26Cr-6Mo-0.18N Alloys for Total Knee Joint.....] - Astawa, I Nyoman Gede Putrayasa; Kartika, Ika; Rokhmanto, Fendy; Purawiardi, Ibrahim; Natalia, Jessica; Alhamidi, Ali (Jurnal Metalurgi, 2019)
Replacement of implant material on knee bones requires some mechanical properties that match with human bones such as wear resistance, high strength, and toughness. The knee joint is a vital part where this part often has a dynamic load, so it needs high hardness and strength to bear the burden of the human body weight. This research aim is to investigate the characteristic of the microstructure and the hardness of Co-Cr-Mo alloy, which consist of precipitates for total knee joint application. As-cast Co-26Cr-6Mo-0.18N and Co-26Cr-6Mo were homogenized at 1200ºC for 12 hours, followed by hot rolling at 1200ºC (90 minutes) and a 50 percent reduction, and then cooling with a variety of cooling media such as ice water, water, and air. After that, several tests were performed to find out the changes in the microstructure and the resulting hardness values through hardness testing, XRD, SEM-EDS observation, and optical microscopy. The results showed that the highest hardness (51 HRC and 61.8 HRC) is obtained when cold-water quenching applied. However, the lowest hardness (42.9 HRC and 49.9 HRC) is conducted using air cooling (aging). The appearance of M23X6 precipitates increases the hardness of Co-26Cr-6Mo-0.18N alloy. Its precipitates can be decreased by adding N.